The Effectiveness of Political Conditionality as an Instrument of Democracy Promotion by the EU: Case Studies of Zimbabwe, Ivory Coast and Niger - (:unkn) unknown (My University, 2015)
0

This study examines the effectiveness of political conditionality by looking at the European Union s suspension of development cooperation with three African, Caribbean and Pacific (ACP ) states (Zimbabwe, Ivory Coast and Niger) perceived to have violated the principles of human rights and democratic principles as laid out in the Cotonou Partnership Agreement adopted in 2000. Analyzing the effectiveness of democracy promotion activities raises the question about its impact upon political processes in the recipient countries. This task is complicated, and it is beyond the aim and capacity of this paper to find a complete answer. Therefore, our conclusions will be cautiously assessed since other factors could intervene and undermine or contribute to the changes in the political system of a given country. Our findings reveal that, in most of the cases, political dialogue and appropriate measures have a modest effect on each country s performance on democratic principles.
Keywords: Uluslararası İlişkiler